2008
DOI: 10.1007/s10457-008-9152-3
|View full text |Cite
|
Sign up to set email alerts
|

Combining napier grass with leguminous shrubs in contour hedgerows controls soil erosion without competing with crops

Abstract: We established hedges/barriers of calliandra (Calliandra calothyrsus Meissner), leucaena (Leucaena trichandra (Zucc.) Urban)) and napier grass (Pennisetum purpureum Schumach) and combination hedges of either calliandra or leucaena with napier grass on slopes exceeding 5% to study the effect of vegetative barriers on productivity of arable steeplands in central Kenya. Hedges/barriers were pruned regularly and biomass incorporated into the plots. Hedge plots were monitored for soil fertility, soil losses and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 34 publications
1
30
1
2
Order By: Relevance
“…However, only a limited number of studies are available about its roots. Thus, some reports describe Napier grass as a shallow rooting species based on the visual observation of its extensive surface root system [14,15], while others consider it a deep rooting species, based again on visual observations [16]. Recently, Ma et al (2012) [17] reported that more than 80% of the root mass of hybrid giant Napier grass was found in soil depths of 0 -0.25 m when evaluating soil to a depth of 1 m, leading to the assumption that this plant is a shallow rooting species.…”
Section: Resultsmentioning
confidence: 99%
“…However, only a limited number of studies are available about its roots. Thus, some reports describe Napier grass as a shallow rooting species based on the visual observation of its extensive surface root system [14,15], while others consider it a deep rooting species, based again on visual observations [16]. Recently, Ma et al (2012) [17] reported that more than 80% of the root mass of hybrid giant Napier grass was found in soil depths of 0 -0.25 m when evaluating soil to a depth of 1 m, leading to the assumption that this plant is a shallow rooting species.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its low requirements for growth conditions and environmental friendliness, Leucaena leucocephala has been a pioneer afforestation tree in dryhot valleys (Bai et al 2004). Many researchers consider it can improve soil quality through SOC sequestration, enhancement of soil fertility and compatibility with soil microbes (Isaac et al 2003;Mutegi et al 2008;Habte and Antal 2010). Relative to the bare soil and Eucalyptus camaldulensis, restoring Leucaena leucocephala to the slope area positively affected SOM content and N content (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This decline may occur through leaching, soil erosion and crop harvesting (Muchena et al, 2005;Mutegi et al, 2008).…”
Section: Introductonmentioning
confidence: 99%